Unveiling the Strategic Model of Political Lies - Firmansyah Firmansyah; Muhammad Sauki; Rahmad Hidayat (Universitas Sultan Ageng Tirtayasa, 2024)
This article delves into the strategic model of political lies, highlighting the intricate nature of this phenomenon within a political framework. Politicians use various strategies to formulate and disseminate lies, ranging from positive campaigns to negative ones. In positive campaigns, lies create a more favorable public perception of politicians, while in negative campaigns, these undermine opponents' standing, instill doubt, and undermine their credibility. Politicians derive immediate advantages from political lies, such as increased popularity and favorable public perceptions, but must also consider potential future costs, including forfeiting public trust and political ramifications. The strategies employed to deal with political lies vary significantly based on political circumstances. Politicians navigate the delicate balance between short-term political advantage and upholding ethical principles in the political sphere. Political lies can quickly garner support and enhance popularity, but they can also undermine public trust, diminish political credibility, and have enduring consequences for a politician's image. Addressing the issue of political lying requires a multifaceted approach that tackles its root causes while safeguarding democratic principles. Voters are crucial to maintaining accountability by exercising their right to vote and assuming control over the democratic process.